Geomorphological Evidence of Localized Stagnant Ice Deposits in Terra Cimmeria, Mars. Issue 6 (12th June 2019) - Adeli, Solmaz; Hauber, Ernst; Michael, Gregory G.; Fawdon, Peter; Smith, Isaac B.; Jaumann, Ralf
Abstract: The presence of snow and ice at midlatitudes of Mars cannot be explained by current climatic conditions, as surface ice is unstable. However, a large variety of debris‐covered glaciers have been observed at both midlatitudes. Here, we report the presence of local, small‐scale, and debris‐covered stagnant ice deposits on the floor of a valley system in Terra Cimmeria. These deposits, termed valley fill deposits (VFD), have a distribution that is restricted to the host valley floor and to the extent of the ejecta blanket associated with Tarq impact crater. The VFD are characterized by convex‐upward morphology, various crevasses, sublimation pits, an average area of a few square kilometers, and occasional ejecta streaks on their surface. Our model age estimation points to two possible time frames for the Tarq impact event; thus, we suggest two formation scenarios for VFD: (I) distribution of ice due to impact into shallow ice during the Middle Amazonian and (II) post‐impact deposition of VFD due to precipitation. In both scenarios, ice preservation is most likely due to a lag of dust and debris deposited in the valley's topographic lows. Scenario I is more consistent with our geomorphological observation of the VFD being overlain by ejecta streaks. Our results highlight the importance of local geological events and conditions in the distribution and preservation of buried ice deposits on Mars and suggest that more small‐scale and debris‐covered ice deposits may exist in the midlatitudes than previously thought. These deposits are of high importance for future human exploration missions to Mars. Plain Language Summary: In the last two decades with the increase of high‐resolution imagery data, more studies report the presence of ice deposits covered by dust and debris on the Martian surface, in both midlatitudes. These deposits must have been formed under different atmospheric conditions, since water ice is not stable in the current surface environment. One of the generally accepted hypotheses for their formation is precipitation induced by variations of Mars' axial tilt known as obliquity. During high obliquity phases, ice would have sublimated from the poles and redeposited in the midlatitudes. Here, we report the presence of small‐scale ice deposits, located on the floor of a valley system in Terra Cimmeria. Although it is clear that these deposits were formed in different climatic conditions, their formation seems to be related to an impact into a shallow subsurface ice layer, redistributing a mixture of ejected material and ice across the region around the impact site. This study shows the importance of local geological processes, for example, impact cratering, in investigations of water ice distribution on Mars. Near‐surface ice reservoirs are of high importance in the search for life and for future human exploration on Mars. Key Points: Small debris‐covered stagnant ice deposits (termed valley fill deposits or VFD) are located inside a valley system in Terra Cimmeria, Mars Morphological properties (convex upward morphology, crevasses, and sublimation pits) suggest a current degradational stage of VFD evolution The location of VFD within the ejecta blanket of Middle Amazonian Tarq crater points to impact into shallow ice as a likely formation process